2012
DOI: 10.3378/027.084.0203
|View full text |Cite
|
Sign up to set email alerts
|

Human Pelvis and Long Bones Reveal Differential Preservation of Ancient Population History and Migration Out of Africa

Abstract: One of the main events in the history of our species has been our expansion out of Africa. A clear signature of this expansion has been found on global patterns of neutral genetic variation, whereby a serial founder effect accompanied the colonization of new regions, in turn creating a within-population decrease in neutral genetic diversity with increasing distance from Africa. This same distinctive pattern has also been described for cranial and dental morphological variation in human populations distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 71 publications
7
90
1
Order By: Relevance
“…As discussed in §3, a wider body conserves heat, whereas a narrower body increases heat loss [8,9]. In a series of exhaustive studies, Ruff has demonstrated that pelvic bi-iliac breadth (intercristal diameter) varies with latitude among modern humans [2,12,13,115], and fossil hominins show the same pattern, with those from warmer climates, including African earliest Homo, having smaller pelvic breadths than those from colder climates [2,12,13,116] (although see [18]). …”
Section: (A) Early Homomentioning
confidence: 97%
See 3 more Smart Citations
“…As discussed in §3, a wider body conserves heat, whereas a narrower body increases heat loss [8,9]. In a series of exhaustive studies, Ruff has demonstrated that pelvic bi-iliac breadth (intercristal diameter) varies with latitude among modern humans [2,12,13,115], and fossil hominins show the same pattern, with those from warmer climates, including African earliest Homo, having smaller pelvic breadths than those from colder climates [2,12,13,116] (although see [18]). …”
Section: (A) Early Homomentioning
confidence: 97%
“…The relationship between body size and shape, overall pelvic size and shape, and birth canal size and shape in modern humans is complex [3,15,17,18,79,[138][139][140][141]. With the evolution of the modern pelvis, the size of the birth canal was essentially decoupled from the size of the body: birth canal proportions in modern humans do not necessarily correlate with body proportions [138,141,142].…”
Section: The Evolution Of the Modern Human Pelvismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to crania, postcrania are frequently labelled as exceedingly variable and unreliable for assessing population affinity, owed primarily to the extreme plasticity exhibited by the appendicular skeleton [24][25][26]. For example, long bone lengths and epiphyseal breadths have been correlated to climate, specifically minimum average temperatures [27]. Similarly, stature is frequently correlated with socioeconomic status (SES), where lower SES typically results in shorter stature [28,29].…”
Section: Introductionmentioning
confidence: 99%